The diatom genus Luticola D.G. Mann (Bacillariophyceae) in the Western Ghats of India and its biogeography. Issue 2 (3rd April 2021) - Lokhande, Vini; Radhakrishnan, Cheran; Kociolek, J. Patrick; Lowe, Rex; Karthick, Balasubramanian
ABSTRACT: Nine species of the diatom genus Luticola D.G.Mann were collected from wet walls and other subaerial habitats from the Western Ghats of India and analysed using light and scanning electron microscopy. Of these, seven are considered to be new species and they are formally described here. They are compared with congeners based on valve size and shape, and ultrastructural features. Another two species described previously by H.P. Gandhi and originally assigned to the genus Navicula are formally transferred to Luticola . Over 25 species of Luticola have been reported from south-east Asia, most of them endemic to the region. The morphological variation of the genus is considered along with its systematics, biogeography and ecology. It appears that south-east Asia, Antarctica and South America are the areas of endemism for this genus.